Effects of Lasmiditan on Cardiovascular Parameters and Pharmacokinetics in Healthy Subjects Receiving Oral Doses of Propranolol - Tsai, Max; Case, Michael; Ardayfio, Paul; Hochstetler, Helen; Wilbraham, Darren (Clinical pharmacology in drug development, 2020)
Lasmiditan (LY573144/COL‐144) is a high‐affinity, centrally penetrant, selective 5‐HT1F receptor agonist currently under investigation for acute treatment of migraine. Although lasmiditan is not known to induce vasoconstriction, it remains important to understand its effect on cardiovascular parameters because it is likely to be coadministered with β‐adrenergic receptor antagonists used for migraine prophylaxis, such as propranolol. This phase 1, single‐center, open‐label, fixed‐sequence study evaluated the cardiovascular and pharmacokinetic effects of 200 mg lasmiditan in 44 healthy subjects receiving repeated oral doses of twice‐daily 80 mg propranolol under fasting conditions. Coadministration caused statistically significant decreases in mean hourly heart rate relative to propranolol alone, but the maximum magnitude of this effect was –6.5 bpm and recovered to predose levels by 3 to 4 hours before stabilizing. Additionally, short‐lived (≤2.5 hours) statistically significant increases in systolic blood pressure (8.3 mm Hg) and diastolic blood pressure (6.4 mm Hg) were observed following coadministration. Consistent with the largely nonoverlapping metabolic pathways of lasmiditan and propranolol, exposure to either drug was not affected by coadministration. Overall, compared with administration of either drug alone, coadministration was generally well tolerated.